Ministry of Transport Decree No. 468 of the Year 2018 on the Incentives in the Egyptian Maritime Ports = وزارة النقل قرار رقم 468 لسنة 2018 بشأن الحوافز فى الموانئ البحرية المصرية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic